LEGAL STUDY OF DISPUTE RESOLUTION OF M E ACTS AGAINST THE LAW OF PLACING ADVERTISEMENTS WITHOUT RIGHTS - Sitti Samia; Muhammad Sabir Rahman; Aksah Kasim; Bakhtiar Tijjang; Kairuddin Karim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine and analyze the process of resolving disputes over the unlawful act of installing billboards and the legal consequences that occur if the billboard is installed incorrectly without rights. This study uses a normative research type with a legislative approach and an analytical approach. The types of legal sources use primary legal materials, secondary legal materials, and tertiary legal materials. Legal analysis will be studied in a qualitative prescriptive manner. The results of this study are the process of resolving disputes over the unlawful act of installing billboards, namely there are 2 paths or mechanisms, namely identifying or proving that the installation of billboards without rights meets the elements in Article 1364 of the Civil Code. In the settlement there are 2 efforts, namely Non-Litigation Efforts (Outside the Court) by seeking Negotiation, mediation, and Conciliation. However, if the Non-Litigation Effort is not successful and effective, then the Court Effort by filing a civil lawsuit in the Court can be carried out with the initial stage of filing a lawsuit (registration of the lawsuit, appointment of a panel of judges and determination of the trial date and mediation efforts), the examination stage (reading of the lawsuit, the defendant's response, replies and duplicates), the evidence stage (letters, witnesses, experts and others) and the final stage of the Conclusion and decision. After a court decision that has permanent legal force (completed or no legal efforts), then the execution will be carried out according to the wording of the decision and the legal consequences that occur if the error in installing a billboard without rights is the result of civil law related to the error in installing a billboard without rights, namely the perpetrator or installer is obliged to make compensation, stop the use of land without permission while dismantling the billboard without rights and returning the condition of the land or building to its original state.